LAS PUBLICACIONES UNIVERSITARIAS: UN ’MEA CULPA’ - Kalmanovitz, Salomón (La Sociología en sus Escenarios, 2010)
Abstract. Kalmanovitz, a prestigious Colombian economist, raises that in the British universities the slogan was " it publishes or muera", whereas in the national universities era " it publishes and muera". The present reality evaluates the impact that has educational publications in the area of social sciences and the panorama is deficient: anything without greater study of its scientific rigor is published and less why they serve. The author raises that the material incentives degenerated the system and that the university professor must publish independent of the existence of wage incentives. Resumen. Kalmanovitz, un prestigioso economista colombiano, plantea que en las universidades anglosajonas la consigna era "publique o muera", mientras que en las universidades nacionales era "publique y muera". La realidad actual evalúa el impacto que tienen las publicaciones docentes en el área de ciencias sociales y el panorama es deficiente: se publica cualquier cosa sin mayor estudio de su rigor científico y menos para qué sirven. El autor plantea que los incentivos materiales degeneraron el sistema y que el profesor universitario debe publicar independiente de la existencia de incentivos salariales.